Masonry arches and vaults under fire. (15th September 2022) - Fantilli, Alessandro P.; Burello, Nicholas S.
Abstract: Arches and vaults subjected to elevated temperatures are herein investigated. For these elements, widely present in historical buildings, structural models under fire scenario are still undefined, also due to the lack of full-scale tests. Indeed, the simplified procedure generally used to assess the capacity of walls and columns (as reported in the annex C of Eurocode 6 part 1–2) needs to be extended to masonry curvilinear structures. Accordingly, with the aim of predicting the loadbearing capacity of arches and vaults, limit analysis is applied to reduced cross-sections. To validate this approach, new laboratory tests were also carried out on barrel vaults subjected to the standard fire in the intrados, and different distributed loads on the extrados. Similarly to the application of simplified models, a conservative estimation of the fire resistance is generally provided by the proposed approach. Highlights: Full-scale tests were performed on masonry barrel vaults subjected to standard fire. A numerical model, based on the limit analysis, was also introduced. The model provides the resistance under fire actions in accordance with the test data. The model can be used to extend the application of Eurocode 6-1-2 to vaults and arches.